La riqualificazione urbanistico–architettonica della cintura ferroviaria di Milano. Infrastrutture e città dialogano per una nuova qualità del paesaggio urbano - Boatti, Antonello (Ri-Vista. Research for landscape architecture, 2015)
A degree thesis in Architetture (Politecnico di Milano) about the architectonic and urban improvement of the railways bel in Milan, offers the opportunità for a reflection on the complivcated topic between infrastructures and townscape.